My body my business: digital media advocacy for LGBT+ society in Zimbabwe - Mutetwa, Eppnoggia (Midlands State University, 2019)
The Zimbabwean society as always been homophobic and homohysteric in nature since the late nineties with the largely publicised homophobic utterances by the former president Mugabe influencing media discourse in the post-independence era. However, studies examining queer sexual identities and digital media platforms in contemporary times are scarce. Guided by the queer theory, this study qualitatively examines how Gays and Lesbians of Zimbabwe Facebook page and Unheard voices blog are utilised for advocacy. The study also examines the play of sexual identities and power contestations at these platforms. Findings of the study show that alternative media platforms are key when it comes to advocacy for queer sexual minorities in a largely conservative Zimbabwe society.